Changing the world, one laptop at a time - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
When Nicholas Negroponte mooted the idea of a US$100 laptop four years ago, he was met with scepticism. Undaunted, he and his team signed up partners and sponsors. Today, the end product, once described as “impossible”, is said to be inspiration behind netbooks. However, technological advancement was not the driving force behind the XO, as this laptop is called. Negroponte was motivated, instead, by the educational needs of developing nations, seeing that a large number of children in these countries receive little or no education. But just how far can inexpensive laptops go to address the needs of poverty-stricken communities?